2017
DOI: 10.3389/fpsyg.2017.02161
|View full text |Cite
|
Sign up to set email alerts
|

Parental Autonomy Granting and School Functioning among Chinese Adolescents: The Moderating Role of Adolescents’ Cultural Values

Abstract: School adjustment and achievement are important indicators of adolescents’ well-being; however, few studies have examined the risk and protective factors predicting students’ school adjustment and achievement at the individual, familial, and cultural level. The present study examined the influences of individual and familial factors and cultural values on Chinese adolescents’ school functioning (e.g., school adjustment and grades). It also tested whether cultural values moderated the relationship between paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…Another contribution of this study was that our findings provided empirical evidence with mainland Chinese samples to support the coexistence of independent and interdependent SCs. We found that on average Chinese adolescents tended to endorse both types of SC, which was consistent with previous findings arguing for the coexistence of independent and interdependent SCs (Sharkey & Singelis, 1995; C. Wang et al, 2017; Yamada & Singelis, 1999), although they did endorse interdependent SC more strongly than independent SC.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Another contribution of this study was that our findings provided empirical evidence with mainland Chinese samples to support the coexistence of independent and interdependent SCs. We found that on average Chinese adolescents tended to endorse both types of SC, which was consistent with previous findings arguing for the coexistence of independent and interdependent SCs (Sharkey & Singelis, 1995; C. Wang et al, 2017; Yamada & Singelis, 1999), although they did endorse interdependent SC more strongly than independent SC.…”
Section: Discussionsupporting
confidence: 91%
“…These findings suggest that, similar to individualism-collectivism (e.g., Triandis, 1995) and autonomy-relatedness (e.g., Rothbaum & Trommsdorff, 2007), independent and interdependent SCs should not be depicted as mutually exclusive or as opposite ends of a single continuum. It is possible that for middle-class mainland Chinese adolescents, there is more internal consistency between independent and interdependent SCs than them being bipolar (also see Li et al, 2010; C. Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in 2018, when individualistic values and behaviors had become more accepted and appreciated, adolescents could take advantage of the psychological autonomy granted by their parents, which in turn promoted the adolescents to achieve better academic adjustment. In addition, the relation between psychological autonomy granting and academic adjustment may be moderated by other factors, such as adolescents’ cultural values, which may account for the results above (Wang, Do, Bao, Xia, & Wu, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…It is likely that those findings may not generalize to Chinese cultural context. Indeed, studies on the role of parenting practices in relation to youth outcomes in Chinese families have yield mixed findings, suggesting the importance of understanding family functioning within a cultural context (Cheung & McBride-Chang, 2008; Wang et al, 2017). Therefore, the aims of the present study were to examine the effects of parental work–life conflict, as a contextual stressor on youth mental health, including both positive mental health (measured by covitality, or the co-occurrence of positive traits) and mental health symptoms, and academic engagement among a sample of highly educated parents and their adolescents in China.…”
Section: Guiding Theory: Risk and Resilience In Family Well-being Dur...mentioning
confidence: 99%